2010
DOI: 10.1016/j.bbadis.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin, resibufogenin and preeclampsia

Abstract: The bufodienolides are cardiac glycosides which have the ability to inhibit the enzyme, Na(+)/K(+) ATPase (sodium potassium adenosine triphosphatase). They are cardiac inotropes, cause vasoconstriction (and, potentially, hypertension) and are natriuretic. Evidence has accrued over time which supports the view that they are mechanistically involved in volume expansion-mediated hypertension. In this communication, the authors summarize data which support the view that the bufodienolides and, in particular, marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 79 publications
1
24
0
1
Order By: Relevance
“…We then administered MBG to normal animals during early pregnancy and reproduced the "preeclamptic" syndrome (33,47). An important finding in human preeclampsia is evidence for vascular leak, as obtained from the examination of alterations in the hematocrit value (8,33). This alteration was also noted in our "preeclamptic rat" (33,34).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…We then administered MBG to normal animals during early pregnancy and reproduced the "preeclamptic" syndrome (33,47). An important finding in human preeclampsia is evidence for vascular leak, as obtained from the examination of alterations in the hematocrit value (8,33). This alteration was also noted in our "preeclamptic rat" (33,34).…”
mentioning
confidence: 71%
“…It has become increasingly clear over time that these agents may play an important role in the etiopathogenesis of those disorders in which volume expansion (10,14,15,47), ischemia (5,11,39,44,47), tissue injury (8,24,34,39,43), and hypoxia (4) occur. Following upon our thesis that elevated levels of MBG are important, if not the most important factor in the development of preeclampsia in a majority of cases, we examined the postulate that volume expansion (22), leading to the excessive production of MBG (47) from early in pregnancy, sets the stage for much of the sequence of events leading to the disorder (33). The volume expansion of the pregnant rat leads to hypertension, proteinuria, and intrauterine growth restriction (IUGR), the hallmarks of human preeclampsia (47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The significant differences in metabolic behaviors between rat and human suggested that rat could not serve as a preferred surrogate model for in vivo study of RB, and the in vivo pharmacological or toxicological data obtained in rat models previously may be misleading. For example, it has been reported that RB has the capability to antagonize marinobufagenin (5-HRB)-caused hypertension, proteinuria, intrauterine growth restriction, and weight gain in a rat model of human preeclampsia (Vu et al, 2006, Horvat et al, 2010Puschett et al, 2010;Puschett, 2012), but these bioactivities have not been observed in other animals. Our results make it conceivable that marinobufagenin will be generated when RB is administrated in human, whereas 3-epi-RB and its derivatives will be generated in rat, and that It is particularly noted that marinobufagenin (5-HRB), a major metabolite of RB in HLM, is one of the endogenous mammalian bufadienolides (Fedorova et al, 2001;Prassas and Diamandis, 2008;Uddin et al, 2011Uddin et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include some hormones or chemical substances, such as sFlt1 (soluble fms-like tyrosine kinase 1) [4], AT1-AA (angiotensin II AT1 receptor auto-antibody) [6], and cardiac glycosides (marinobufagenin, MBG) [8]. Among these, sFlt1 can cause endothelial dysfunction in the maternal blood vessels by binding vascular endothelial growth factors and placental growth factor [4]; AT1-AA can react with the AT1 receptor in a stimulatory fashion similar to angiotensin II signalling, which could contribute to maternal hypertension [6]; MBG, involved in the pathogenesis of preeclampsia, has been demonstrated to cause hypertension, proteinuria, and intrauterine growth restriction in the rat model of preeclampsia [8]. Augmented release of these factors secondary to the original poor placenta will eventually lead to damage of the endothelium, metabolism dysfunction, and inflammation as well as other typical symptoms.…”
Section: Preeclampsiamentioning
confidence: 99%